Planning a Problem Based Learning (PBL) Model in Biology Subjects in High School: A Case Study - Arwita, Widya; Sitinjak, Abraham Pranata; Amanda, Naziha; Istiara, Rayuni; Mahmudah, Delsa; Nasution, Sheila Desiska; Sianturi, Sri Tama Rotua (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Biology learning in the 21st century demands a shift from conventional teacher-centered methods to student-centered approaches to improve critical thinking and problem-solving skills. The Problem-Based Learning (PBL) model is one relevant approach, but its implementation is highly dependent on the quality of teacher planning. This study intends to describe and analyze in depth the PBL model planning process in biology subjects at high school. This study uses a qualitative approach with a case study method. The research subjects are biology teachers and the school's internal MGMP team. Data collection was conducted through in-depth interviews, non-participatory observation during planning meetings, and document analysis in the form of lesson implementation plans. The results of the study indicate that the PBL planning process at High School 5 Medan goes through several crucial stages: (1) Identification of essential materials suitable for PBL; (2) Formulation of problems (scenarios) that are authentic, contextual, and relevant to the student's environment; (3) Design of systematic learning steps according to PBL syntax; and (4) Development of authentic assessment instruments that focus on process and product. The main challenges faced by teachers in planning are time allocation and alignment problems with the learning outcomes set by the curriculum. This case study concludes that thorough and collaborative planning is an essential key to the successful implementation of PBL and recommends the need for ongoing professional development support for teachers in designing innovative learning.